PENGARUH TOTAL QUALITY MANAGEMENT TERHADAP KINERJA PERUSAHAAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING (Studi Empiris di PT. So Good Food Boyolali) - pratama, windra (Universitas Slamet Riyadi, 2020)
This research is conducted in order to find out the significance of the influence of aspects of customer satisfaction, respect for each person, management based on facts, and continuous improvement to the performance of the company PT. So Good Food Boyolali is moderated by organizational commitment. The population is permanent employees of PT. So Good Food numbered 150 people. Samples were taken with 109 people representing Proportionate Stratified Random Sampling. Data collection techniques using a questionnaire. The analysis technique uses multiple linear regression test and absolute difference value regression. Conclusion of the results of the study showed: Customer satisfaction has a significant effect on company performance, Respect for everyone has a significant effect on company performance, Management based on fact significant influence on company performance, Continual improvement has a significant effect on company performance, Organizational commitment has a significant effect on company performance, Focus on customers does not significantly influence the performance of the company is moderated by organizational commitment, Management based on facts has no significant effect on company performance moderated by organizational commitment, Management based on facts has no significant effect on company performance moderated by organizational commitment, Continual improvement has no significant effect on company performance moderated by organizational commitment. Â Keywords: Total Quality Management, company performance, organizational commitment.